2021
DOI: 10.9734/ijtdh/2021/v42i2330562
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Weather in the Spread of Lassa Fever in Parts of Northern Nigeria

Abstract: This study employed multiple regression analysis to evaluate the impact of weather variables (relative humidity, rainfall amount and maximum temperature) on the reported number of Lassa fever cases and to assess the strength of relationship between same for thirteen states in northern Nigeria (Adamawa, Bauchi, Jigawa, Borno, Kaduna, Katsina, Kano, Kebbi, Sokoto, Taraba, Yobe, Zamfara and Gombe states) over a five-year period (2016-2020). Secondary data on Lassa fever disease and weather variables were describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The primary zoonotic transmission from the reservoir to humans through the faeco-oral route, rodent bites and medium risk of Lassa fever incidence. This agrees with Adebimpe [12]; Nchom, et al [73]; Fichet Calvet, [74], and Kerneis, et al [75] wherein a link was established between Lassa fever and the pattern of rainfall as a major abiotic factor influencing the incidence of Lassa fever. This was supported by the observation of the host rodent species ecology.…”
Section: Social and Ecological Factors Contributing To The Spread Of ...supporting
confidence: 89%
See 1 more Smart Citation
“…The primary zoonotic transmission from the reservoir to humans through the faeco-oral route, rodent bites and medium risk of Lassa fever incidence. This agrees with Adebimpe [12]; Nchom, et al [73]; Fichet Calvet, [74], and Kerneis, et al [75] wherein a link was established between Lassa fever and the pattern of rainfall as a major abiotic factor influencing the incidence of Lassa fever. This was supported by the observation of the host rodent species ecology.…”
Section: Social and Ecological Factors Contributing To The Spread Of ...supporting
confidence: 89%
“…Zhao, et al [77] in their study noted that in Nigeria, LASV outbreaks have been known to occur during the dry season between November and May, and a positive association between rainfall and the transmission of LASV was ascertained. Nchom, et al [73] also observed that there was a hike in cases during the dry season when rainfall has significantly reduced The primary transmission of LASV has not been fully comprehended [25] as several environmental factors play a major role in determining the rate of transmission; as common with all emerging diseases, any increase in cases both suspected and confirmed across an endemic region must be closely monitored to establish a pattern, hence the need to study environmental factors that considerably contribute to the spread and sustenance of LASV in endemic areas. Another consideration is hygiene practices, food packaging, food storage and waste disposal practices, which have the potential to increase the disease incidence [63][64][65][66][67][68][69][70].…”
Section: Social and Ecological Factors Contributing To The Spread Of ...mentioning
confidence: 99%
“…Fichet-Calvet and Rogers (2009) demonstrated that recorded LF outbreaks in human populations occurred in areas receiving annual rainfall between 1500 and 3000 mm 8 . Changes in temperature can affect the immune response of humans and rodents, potentially influencing the severity and outcomes of LF infections 39 . Temperature plays a crucial role in the transmission and incidence of LF, which is primarily carried by rodents and transmitted to humans through contact with contaminated excreta or urine.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence suggesting that higher temperatures may be associated with increased LF incidence, with the highest incidence observed during the hottest months of the year 40 . Higher temperatures can enhance the reproductive rates of rodent populations, leading to an increase in the number of infected animals and potentially raising the risk of transmission to humans 39 . Understanding these temperature-related dynamics can help shape strategies aimed at reducing the urbanisation of LF and mitigating the risk of outbreaks in urban areas.…”
Section: Discussionmentioning
confidence: 99%